2020
DOI: 10.1037/xlm0000748
|View full text |Cite
|
Sign up to set email alerts
|

Detecting spelling errors in compound and pseudocompound words.

Abstract: Three experiments using a spelling error detection task investigated the extent to which morphemes and pseudomorphemes affect word processing. We compared the processing of transparent compound words (e.g., doorbell), pseudocompound words (e.g., carpet), and matched control words (e.g., tomato). In half of the compound and pseudocompound words, spelling errors were created by transposing adjacent letters and in half of the control words, errors were created by transposing letters at the same location as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 53 publications
(89 reference statements)
1
15
0
Order By: Relevance
“…In fact, for semantically opaque compounds such as ladybird or windfall, these whole-word meanings differ dramatically from their compositionallyobtained meanings (for an overview on semantic transparency/opacity, see Schäfer, 2018). However, from a processing perspective, it still makes sense to immediately initiate a compositional process whenever a compound is encountered (see Chamberlain, Gagné, Spalding, & Lõo, 2019;Günther & Marelli, 2019a). Assuming that the main purpose of language is to convey meaning, language processing would be geared towards understanding the linguistic stimuli we encounter (Libben, 2014): Before the whole-word lexical entry has been accessed, one cannot know whether the compound is familiar or not -and thus, whether there even is such an entry (see El-Bialy, Gagné, & Spalding, 2013).…”
mentioning
confidence: 99%
“…In fact, for semantically opaque compounds such as ladybird or windfall, these whole-word meanings differ dramatically from their compositionallyobtained meanings (for an overview on semantic transparency/opacity, see Schäfer, 2018). However, from a processing perspective, it still makes sense to immediately initiate a compositional process whenever a compound is encountered (see Chamberlain, Gagné, Spalding, & Lõo, 2019;Günther & Marelli, 2019a). Assuming that the main purpose of language is to convey meaning, language processing would be geared towards understanding the linguistic stimuli we encounter (Libben, 2014): Before the whole-word lexical entry has been accessed, one cannot know whether the compound is familiar or not -and thus, whether there even is such an entry (see El-Bialy, Gagné, & Spalding, 2013).…”
mentioning
confidence: 99%
“…These findings held even after controlling for semantic, orthographic, phonological, and syllabic factors. Furthermore, Chamberlain et al (2020) found that compounds and pseudocompounds exhibited different effects in a spelling error detection task; compounds showed a processing advantage relative to their matched controls whereas pseudocompounds did not show this facilitation. Also, letter transpositions at the morpheme boundary removed the processing advantage for compounds relative to their controls, but created a processing disadvantage for pseudocompounds (e.g., patnry was slower than its matched control), suggesting that there is some advantage to the presence of morphemes which is removed by the transposition of the boundary letters.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to opaque compounds, exposure to pseudocompounds resulted in significant inhibition of the target car. These findings suggest that the processing system establishes a morphological structure for all compounds, including opaque compounds and even pseudocompounds; however, this may lead to a processing cost when the established structure is incompatible with the true morphemic structure of the word (see also Chamberlain et al, 2020).…”
Section: Semantic Transparencymentioning
confidence: 99%